Application of the analytic hierarchy approach to the risk assessment of Zika virus disease transmission in Guangdong Province, China. Issue 1 (December 2017) - Li, Xing; Liu, Tao; Lin, Lifeng; Song, Tie; Du, Xiaolong; Lin, Hualiang; Xiao, Jianpeng; He, Jianfeng; Liu, Liping; Zhu, Guanghu; Zeng, Weilin; Guo, Lingchuan; et al.
Abstract Background An international spread of Zika virus (ZIKV) infection has attracted global attention in 2015. The infection also affected Guangdong province, which is located in southern China. Multiple factors, including frequent communication with South America and Southeast Asia, suitable climate (sub-tropical) for the habitat ofAedes species, may increase the risk of ZIKV disease transmission in this region. Methods An analytic hierarchy process (AHP) method was used to develop a semi-quantitative ZIKV risk assessment model. After selecting indicators, we invited experts in related professions to identify the index weight and based on that a hierarchical structure was generated. Then a series of pairwise comparisons were used to determine the relative importance of the criteria. Finally, the optimal model was established to estimate the spatial and seasonal transmission risk of ZIKV. Results A total of 15 factors that potentially influenced the risk of ZIKV transmission were identified. The factor that received the largest weight was epidemic of ZIKV in Guangdong province (combined weight [CW] =0.37), followed by the mosquito density (CW = 0.18) and the epidemic of DENV in Guangdong province (CW = 0.14). The distribution of 123 districts/counties' RIs of ZIKV in Guangdong through different seasons were presented, respectively. Conclusions Higher risk was observed within Pearl River Delta including Guangzhou, Shenzhen and Jiangmen, and the risk is greater in summer and autumn compared to spring and winter.